PENURUNAN PERSAMAAN DARCY DARI PERSAMAAN NAVIER-STOKES UNTUK RESERVOIR ALIRAN LINIER DAN RADIAL - Listiana Satiawati; Prayang Sunni Yulia (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2019)
Calculation of hydrocarbon flow in the form of oil or gas in Petroleum Engineering is used the Darcy equation. Deriving the Navier Stokes equation produces a general equation that cannot be used for special conditions, for example linear or radial flow because the formulation is different. In this paper, the Darcy equation obtained through experimental evidence is derived from the Navier Stokes equation with several assumptions and simplifications . The calculation in this paper uses a numerical solution, which uses Fortran language, as one approach. Then by using field data, the Darcy equation is used in calculating the flow rate and the velocity of linear fluid in the reservoir. And also the calculation of the pressure from the well to the outermost point of the reservoir with radial fluid flow, so that the pressure gradient data can be obtained from the well to the outermost point of the reservoir.